ESTUDIO ANALÍTICO DE LA POBREZA EN EL ECUADOR EN EL PERÍODO 2007-2017 - Guevara Criollo, Jessica Guadalupe (2020)
This research results from a historical analysis of the evolution of poverty, taking into account a wide variety of factors. The percentages of poverty that Ecuador had in 10 years were analyzed, poverty was explained through annual statistical data to determine the behavior of poverty by analyzing different social groups, poverty was analyzed by age, sex, ethnicity, central government spending, etc. Concepts of poverty from various authors and governmental organizations are interpreted to have a broad vision. A theoretical analysis of the causes and consequences of poverty is carried out, and the methodology used by Ecuador to measure poverty levels is analyzed. The method used to carry out the research was: the scientific method, historical method, analytical- synthetic method. The study is descriptive with a qualitative focus. The data used was from reliable institutions such as the Institute of Statistics and Census, the Central Bank of Ecuador, and the Accountability Report. Finally, in the discussion of the results, The annual analysis; was carried out over ten years. Showing the economic growth in the years (2007-2017) since the country's GDP had grown and the poverty rates for basic needs decreased these years, indicating that the government increased its economic and social development.